Mechanism of White Matter Injury and Promising Therapeutic Strategies of MSCs After Intracerebral Hemorrhage - Li, Jing; Xiao, Linglong; He, Dian; Luo, Yunhao; Sun, Haitao (Frontiers in Aging Neuroscience, 2021)
Intracerebral hemorrhage (ICH) is the most fatal subtype of stroke with high disability and high mortality rates, and there is no effective treatment. The predilection site of ICH is in the area of the basal ganglia and internal capsule (IC), where exist abundant white matter (WM) fiber tracts, such as the corticospinal tract (CST) in the IC. Proximal or distal white matter injury (WMI) caused by intracerebral parenchymal hemorrhage is closely associated with poor prognosis after ICH, especially motor and sensory dysfunction. The pathophysiological mechanisms involved in WMI are quite complex and still far from clear. In recent years, the neuroprotection and repairment capacity of mesenchymal stem cells (MSCs) has been widely investigated after ICH. MSCs exert many unique biological effects, including self-recovery by producing growth factors and cytokines, regenerative repair, immunomodulation, and neuroprotection against oxidative stress, providing a promising cellular therapeutic approach for the treatment of WMI. Taken together, our goal is to discuss the characteristics of WMI following ICH, including the mechanism and potential promising therapeutic targets of MSCs, aiming at providing new clues for future therapeutic strategies.